2007
DOI: 10.1213/01.ane.0000287659.14893.65
|View full text |Cite
|
Sign up to set email alerts
|

The 8-Item Short-Form Health Survey and the Physical Comfort Composite Score of the Quality of Recovery 40-Item Scale Provide the Most Responsive Assessments of Pain, Physical Function, and Mental Function During the First 4 Days After Ambulatory Knee Surgery with Regional Anesthesia

Abstract: For ACLR outpatients receiving regional anesthesia, the SF-8 is sufficient to assess postoperative pain and physical function. Adding the QoR physical comfort composite will help assess short-term side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 28 publications
1
30
0
1
Order By: Relevance
“…SF-8 has been found to be reliable and valid 40,41 and is designed to assess the eight subscales from widely-used SF-36: general health; physical functioning; role limitations due to physical problems; pain; energy; social functioning; emotional well-being; and role limitations due to emotional problems. Following the standard guidelines, the first four items were averaged to compute a composite score for physical health (α = .85), and the latter four items were averaged to compute a composite score for mental health (α = .76).…”
Section: Self-reported Mental and Physical Healthmentioning
confidence: 99%
“…SF-8 has been found to be reliable and valid 40,41 and is designed to assess the eight subscales from widely-used SF-36: general health; physical functioning; role limitations due to physical problems; pain; energy; social functioning; emotional well-being; and role limitations due to emotional problems. Following the standard guidelines, the first four items were averaged to compute a composite score for physical health (α = .85), and the latter four items were averaged to compute a composite score for mental health (α = .76).…”
Section: Self-reported Mental and Physical Healthmentioning
confidence: 99%
“…Numerical values were assigned to each response corresponding to magnitude of pain intensity (0 being "none" and 5 "very severe"). Bost et al 5 found that in the first 4 days after ACL reconstruction the SF-8 bodily pain question was reliable (Chronbach's .7), valid (r = 0.65), and equally responsive (SF-8: SRM, 0.53; numeric rating scale: SRM, 0.60), when compared to a 10-point numeric rating scale during knee movement. naire data.…”
Section: Self-report Questionnairesmentioning
confidence: 99%
“…(3,5,18,20) The correlation of the QoR-40 with the VAS of surgical recovery was acceptable and superior when compared to values obtained in other cultures, whose results ranged from r=0.45 to 0.68. (3,5,15,16,18,19) …”
Section: Discussionmentioning
confidence: 74%
“…In an Australian study, the same dimensions resulted in low alpha values; questions that evaluated pain in non-surgical areas showed propensity in reducing consistency regarding questions that evaluated pain in an overall way. (20) Regarding items that describe effects of medications and anesthetic procedures, it is believed that these events could be identified in the postoperative period of early surgeries, and in fact they were, because they presented variability of responses in this period. The acceptable evolution of postoperative recovery predicts that these events will not occur late.…”
Section: Discussionmentioning
confidence: 99%